Evaluation of whole-genome sequence to predict drug resistance of nine anti-tuberculosis drugs and characterize resistance genes in clinical rifampicin-resistant Mycobacterium tuberculosis isolates from Ningbo, China - Che, Yang; Lin, Yi; Yang, Tianchi; Chen, Tong; Sang, Guoxin; Chen, Qin; He, Tianfeng (Frontiers in Public Health, 2022)
SETTING: Programmatic management of drug-resistant tuberculosis in Ningbo, China. OBJECTIVE: The comprehensive information of M.tuberculosis isolates by Whole-genome sequencing (WGS), especially Rifampicin-resistant tuberculosis (RR-TB) have not been studied in Ningbo, China. The goal of this study was to provide a baseline characterization of circulation known and putative drug resistance mutations, and to identify potential RR-TB transmission chains. DESIGN: WGS was utilized to predict drug resistance using an online 'TB-Profiler' tool after phenotypic DST against nine anti-drugs among 59 clinical isolates. For each drug, the consistency, sensitivity, specificity, positive and negative predictive values of WGS were compared with those of the conventional drug susceptibility test. RESULTS: The overall sensitivities and specificities for WGS were 95.92% and 90.00% for isoniazid (INH), 100.00% for rifampicin (RIF), 100.00% and 64.10% for ethambutol (EMB), 97.37% and 100.00% for streptomycin (SM), 75.00% and 100.00% for amikacin (AM), 80.00% and 96.30% for capreomycin (CAP), 100.00% and 97.22% for levofloxacin (LFX), 93.33% and 90.91% for prothionamide (PTO), 70.00% and 97.96% for para-aminosalicylic acid ( PAS), respectively. Around 89.83% isolates (n=53) and 6 (10.17%) belonged to lineage two (East-Asian) lineage four (Euro-American), respectively. CONCLUSION: WGS is a reliable method for predicting resistance to INH, RIF, EMB, SM, AM, CAP, LFX, PTO, and PAS with high consistency, sensitivity and specificity. There was no transmission occurred among the RR-TB in Ningbo,China.